Groundwater development through sprinkler irrigation: consequences of a lack of a governance structure in Kalpitiya, Sri Lanka - Aheeyar, Mohamed M. M.; Manthrithilake, Herath; Pathmarajah, S.; Makin, Ian W. (2016)
Groundwater provides nearly 100 % of the water supplies in some districts of Sri Lanka and is a major source of domestic water in all other districts. However, the resource remains largely neglected and invisible to society and policymakers. Groundwater offers the advantage of being a more reliable and readily available resource for agriculture, and offers the basis for a ‘silent revolution’ in many areas. A groundwater-supported agricultural boom has, while imparting a large number of benefits, created its own set of obstinate problems, including over-exploitation and depletion of groundwater resources. In some districts, over-exploitation is putting the livelihoods of farmers that have come to depend on groundwater resources in jeopardy. Micro-irrigation technologies have been widely promoted as a means of reducing water demand by enhancing farm-level water-use efficiency. These technologies are proven to improve irrigation uniformity; increase irrigation application efficiency, by reducing soil evaporation and seepage losses; and increase crop productivity. It is assumed that using these technologies will enable water to be reallocated for other uses. The Government of Sri Lanka has made repeated attempts to promote micro-irrigation as a means of improving irrigation performance to minimize water scarcity in areas of the Dry Zone. These attempts have involved providing substantial heavy subsidies, but have met with little success in terms of adoption of ‘professionally designed’ installations. However, in Kalpitiya, farmers have adopted a locally designed sprinkler technology within a short period of time without subsidies and professional design inputs. This paper reviews the evolving agricultural boom as a result of groundwater and sprinkler irrigation that has occurred on the Kalpitiya peninsula. The development of a farmer-led sprinkler technology is assessed with reference to improving livelihoods of the people, and the potential consequences on sustainable management of groundwater resources. The experiences in Kalpitiya show that, in the absence of effective groundwater governance and policies, supported with appropriate institutions, micro-irrigation has enabled the expansion of the cultivated area and crop intensification. This has increased, rather than decreased, net water use on the peninsula. The estimated increase in water withdrawals is 14,490 m3/ha /y. This indicates that promoting efficient technologies alone is not sufficient to achieve water savings, which requires control of overall abstractions and recharge levels to stabilize aquifer storage. In the absence of an appropriate regulatory framework and lack of political will to manage groundwater, it is recommended that the social framework and community governance arrangements are developed and strengthened to enable sustainable use of groundwater resources.